A relação entre orientação para o mercado e as atividades de marketing de construtoras de condomínios residenciais de Londrina e Maringá - Munhoz, Alexandre João (2009)
The market orientation scales intend to evaluate the application of the "Marketing concept" within the company. In particular the MARKOR scale, search for a measurement through the information flow inside companies. However, there is many marketing activities, recognized by various authors in this area, wich are not considered in this evaluation. Therefore, this research had as main objective revealing the relation between the practices of marketing activities with the market orientation level within companies. For that, a research in the literature was made o provide an overview of the studies of Market Orientation in Brazil and the world, presenting too a review of the concepts of Marketing Activities by several authors in the area. Then residential condominium constructers were surveyed in the cities of Londrina and Maringá using the MARKOR scale, to market orientation, a marketing activities scale and a business performance scale. This research's nature was quantitative, looking to describe the characteristics of the population and searching the variables relations through the Fisher's exact test, to check this relation, and the Cramer's V, to evaluate its significance. The results didn't confirm a significant relationship between the two constructs in the sample, and therefore opened up many other questions about the subject. It was also not confirmed the relationship between the market orientation and organizational performance, however, a significant relationship was found between the latter and the level of Marketing Activities.